2017
DOI: 10.31254/phyto.2017.6605
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Lactobacillus spp. from curd and its pharmacological application in probiotic chocolate.

Abstract: The isolated and identified bacteria from curd sample are of Lactobacillus sp. The bacteria of this spp. are lactic acid producers. These sp. resembles to Lactobacillus acidophilus. A probiotic is a microorganism known to be friendly and beneficial to its host when consumed. In today's time, probiotics are a very popular subject of research among scientists and pharmaceutical companies. Due to the over consumption of antibiotics, the normal micro flora of body does not survive. The spores obtained from pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A study by Kuji et al (2021) have observed Lactobacillus plantarum 299 and Lactobacillus reuteri DSM 17938 degrading phenolic acids via hydrolysis of phenols to either dihydrocaffeic acid or 4vinylcatechol and 4-ethylcatechol. In the contrary, some reports stated that Lactobacillus strains were only able to tolerate phenol concentration to 0.4% and the viability decreased by 50% at 0.6% (Hoque et al, 2010;De et al, 2017;Mannan et al, 2017;Reuben et al, 2020). Regarding solvent systems, P. pentosaceus strains were not able to tolerate all the solvents at the highest concentration (4%) (Figure 5).…”
Section: Resistance Of Isolated Probiotic Bacteria To Phenol and Solv...mentioning
confidence: 92%
“…A study by Kuji et al (2021) have observed Lactobacillus plantarum 299 and Lactobacillus reuteri DSM 17938 degrading phenolic acids via hydrolysis of phenols to either dihydrocaffeic acid or 4vinylcatechol and 4-ethylcatechol. In the contrary, some reports stated that Lactobacillus strains were only able to tolerate phenol concentration to 0.4% and the viability decreased by 50% at 0.6% (Hoque et al, 2010;De et al, 2017;Mannan et al, 2017;Reuben et al, 2020). Regarding solvent systems, P. pentosaceus strains were not able to tolerate all the solvents at the highest concentration (4%) (Figure 5).…”
Section: Resistance Of Isolated Probiotic Bacteria To Phenol and Solv...mentioning
confidence: 92%